Gambaran Hasil HPV Test dengan PAP Test pada Pasien dengan Lesi Prakanker Serviks di RSUP Dr M Djamil Padang - Angga Trifianda Prima; Andi Friadi (Universitas Andalas, 2019)
Objective: To determine the description of the HPV Test results with the PAP Test in patients with cervical precancerous lesions at Dr. M. Djamil Padang.Methods: This study used a descriptive method with a sample of all patients with cervical precancerous lesions who had the HPV test and PAP test results in Dr. M. Djamil Padang from January 1, 2015 - December 31, 2017. Data were taken from the patient's medical records, including diagnosis, PAP test results using the Hybrid Capture (HC) method, and HPV test. Results: During the study period, 80 patients had PAP test results leading to precancerous lesions and cervical cancer. Of the 80 patients, only 4 cases with positive HPV test results. Conclusion: In this study, there were many cervical precancerous lesions with negative HPV test results.Keywords: Cervical precancerous lesions, PAP test, the HPV test